RANCANG BANGUN APLIKASI PENGELOLA CUCIAN MOBIL MENGGUNAKAN BORLAND DELPHI BERBASIS WINDOWS - Fahmi Ramadhan; Alona Situmeang; Jamilah Jamilah (Asosiasi Dosen Muda Indonesia, 2022)
Car wash is a business that involves many transactions and requires good data processing. The use of technology in managing car washes is very helpful in data processing. The process of managing data on a car wash that is done manually can cause errors in calculating income, worker salaries or data loss. The aim of the research is to design an application that can be used to manage data in car wash businesses such as employee attendance, washing transactions, employee income and salaries. The research method used is analysis, design, implementation, and testing. This application is made using the programming language Borland Delphi 7 and Microsoft Access database. The results of application testing using the blackbox testing method are carried out, the application functions properly on a Windows-based laptop.